2018
DOI: 10.1080/00140139.2018.1472804
|View full text |Cite
|
Sign up to set email alerts
|

What went right? An analysis of the protective factors in aviation near misses

Abstract: Learning from successful safety outcomes, or what went right, is an important emerging component of maintaining safe systems. Accordingly, there are increasing calls to study normal performance in near misses as a part of safety management activities. Despite this, there is limited guidance on how to accomplish this in practice. This article presents a study in which using Rasmussen's risk management framework to analyse 16 serious incidents from the aviation domain. The findings show that a network of protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A recent analysis of 12 aviation reports of near misses found that accidents were averted in each case because of effective vertical integration. 16 "Contrary to the common belief that a single act can save the day," the authors found that "communication (both within and across levels) and feedback and control loops develop a network of protective factors which can lead to accident prevention." 16(p199) Errors are not interrupted only by "heroic moments of inspired action" 16(p199) ; they are interrupted when protective factors interact to steer the system toward safety.…”
Section: Preemptive Risk Reductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent analysis of 12 aviation reports of near misses found that accidents were averted in each case because of effective vertical integration. 16 "Contrary to the common belief that a single act can save the day," the authors found that "communication (both within and across levels) and feedback and control loops develop a network of protective factors which can lead to accident prevention." 16(p199) Errors are not interrupted only by "heroic moments of inspired action" 16(p199) ; they are interrupted when protective factors interact to steer the system toward safety.…”
Section: Preemptive Risk Reductionmentioning
confidence: 93%
“…Instead of looking for causative or contributory factors after a failure, preemptive risk reduction looks for factors that are protective to better understand how things go right. 16 It is Three competing boundaries influence the state of safety in any complex system. The black "X" identifies a system in which risk is contained, one in which the competing boundaries are in balance.…”
Section: Preemptive Risk Reductionmentioning
confidence: 99%
“…The extent of the effect on a person and his colleagues is pervasive and versatile. Then again, some people essentially explore comfort and relief in the workplace if situational stress is an outcome of factors outside of their employment [9,40].…”
Section: Psychological Conditionsmentioning
confidence: 99%
“…Within the CRM-DYMO model it is specifically concerned with the transmission of data/information. Effective communication has been identified as a protective factor for the safe and efficient conduct of a flight (Thoroman et al, 2019). Good teamworking also promotes situation awareness and hence decision making (see Kanki, 2010).…”
Section: Communicationmentioning
confidence: 99%